Di(2‐ethylhexyl) phthalate‐induced apoptosis in rat INS‐1 cells is dependent on activation of endoplasmic reticulum stress and suppression of antioxidant protection. Issue 3 (23rd November 2014) - Sun, Xia; Lin, Yi; Huang, Qiansheng; Shi, Junpeng; Qiu, Ling; Kang, Mei; Chen, Yajie; Fang, Chao; Ye, Ting; Dong, Sijun
Abstract Di(2‐ethylhexyl) phthalate (DEHP) is used as plasticizer and is ubiquitously found in the environment. Exposure to DEHP has been linked to an increased incidence of type 2 diabetes. Pancreatic β‐cell dysfunction is a hallmark of type 2 diabetes; however, it is unknown whether DEHP exposure contributes to this risk. Here, we aimed to investigate the cytotoxic effects of DEHP on INS‐1 cells and to further explore the related underlying mechanisms. INS‐1 cells were exposed to 0, 5, 25, 125 or 625 μM DEHP for 24 hrs. Cell viability, glucose‐stimulated insulin secretion, reactive oxygen species (ROS) generation, cellular antioxidant response, Ca2+ homoeostasis and the levels of genes and proteins involved in endoplasmic reticulum (ER) stress were measured. The results showed that DEHP decreased insulin secretion and content and induced apoptosis in INS‐1 cells in a dose‐dependent manner. Furthermore, ROS generation was increased and Nrf2‐dependent antioxidant defence protection was dysregulated in INS‐1 cells after DEHP exposure. Most importantly, DEHP effectively depleted ER Ca2+ and triggered the ER stress response as demonstrated by the elevated transcription and translation of the ER chaperone GRP78 and GRP94, the increased phosphorylation of protein kinase R‐like endoplasmic reticulum kinase (PERK) and its downstream substrate eukaryotic translation initiation factor 2α (eIF2α), as well as the increased levels of activating transcription factor 4 (ATF4) and C/EBP homologous protein (CHOP). Taken together, DEHP exerted toxic effects on INS‐1 cells by inducing apoptosis, which is dependent on the activation of the PERK–ATF4–CHOP ER stress signalling pathway and the suppression of Nrf2‐dependent antioxidant protection.